(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
In this article, the biological classification of the tomato plant (Solanum Iycopersicum), history of its origin, distribution of varieties on the surface of the earth and its place in agriculture among cash crops, the importance of macro and micro elements in its composition for human health, as well as its role in the food industry is cited.